ChemInform Abstract: Rh‐Catalyzed One‐Pot Sequential Asymmetric Hydrogenation of α‐Dehydroamino Ketones for the Synthesis of Chiral Cyclic trans‐β‐Amino Alcohols. Issue 31 (14th July 2016) - Hu, Qiupeng; Chen, Jianzhong; Zhang, Zhenfeng; Liu, Yangang; Zhang, Wanbin
Abstract: The desired trans‐alcohols are obtained with moderate diastereoselectivity and, in most cases, with excellent enantioselectivity.